Development of Prototype Protection Scheme for Distributed Generation in Low Voltage Distribution Network - Joshua Suneil A/L Selvan; Lam Hong Yin (Progress in Engineering Application and Technology, 2024)
The low-voltage LV distribution network is the last stage of the power network, which is connected directly to the end-user customers and supplies many dispersed small-scale loads. It is a worldwide practice to inject renewable energy sources RESs into the electricity grid, which is a subset of distributed generation DG capacity. In addition, different types of low-carbon technologies LCTs, such as electric vehicles are becoming widely used. A significant portion of RES and LCTs is penetrated into the LV distribution network, which poses a wide range of challenges. To address these challenges, there is a persistent need to develop traditional planning and operation frameworks to cope with these new technologies. Hence the setting for the traditional protection relays has become unsuitable to the future distribution system with high penetration of distributed generation. In order to ensure the quality and reliability of the power supply, the issues raised by DG need to be solved. In this study, the impacts of high penetration of distributed generated to existing protection schemes are investigated. The new protection schemes are designed for the distribution network with high penetration of DG. As for this project we propose developing a prototype which can ensure protection for distributed generation in the in (LV) distribution network. The prototype is designed in a way to detect overvoltage, undervoltage, overcurrent, undercurrent and power which is caused by distributed generation, and when the relay detects an overvoltage or any other fault in the circuit, it displays in the LCD screen, and the current flow is cut off. Summarily, this project can provide a better and more efficient protection for end-users